2008
DOI: 10.1123/tsp.22.3.316
|View full text |Cite
|
Sign up to set email alerts
|

“Bouncing Back” from Adversity: Athletes’ Experiences of Resilience

Abstract: The purpose of this study was to explore athletes’ perceptions and experiences of resilience. Ten high-level athletes were interviewed regarding the most difficult adversities that they had ever had to overcome in sport. Richardson and colleagues’ (Richardson, Neiger, Jensen, & Kumpfer, 1990) resiliency model served as a guiding theoretical framework in the process of data collection and analysis. Inductive analysis (Patton, 2002; Thomas, 2006) was used to explore the data for key themes and patterns of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
227
4
27

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(268 citation statements)
references
References 46 publications
10
227
4
27
Order By: Relevance
“…Related research also points to the significance of athletic [163][164][165][166][167][168][169][170] and exercise [171][172][173] identity, and this has fed into research that draws on notions of social identity to understand both exercise behaviour [174] and health behaviour [175], as well as event participation (e.g., in the Gay Games [176]). Along lines suggested above, the social identity approach can also be used to inform the current interest in personal [177] and collective [178] resilience in sport. Here, research has demonstrated that social identity and membership of multiple groups enhances resilience in the face of pain, and also aids heart rate recovery in athletes following winter sports training [179].…”
Section: New Frontiers: Towards a Broader Application Of The Social Imentioning
confidence: 99%
“…Related research also points to the significance of athletic [163][164][165][166][167][168][169][170] and exercise [171][172][173] identity, and this has fed into research that draws on notions of social identity to understand both exercise behaviour [174] and health behaviour [175], as well as event participation (e.g., in the Gay Games [176]). Along lines suggested above, the social identity approach can also be used to inform the current interest in personal [177] and collective [178] resilience in sport. Here, research has demonstrated that social identity and membership of multiple groups enhances resilience in the face of pain, and also aids heart rate recovery in athletes following winter sports training [179].…”
Section: New Frontiers: Towards a Broader Application Of The Social Imentioning
confidence: 99%
“…One of the challenges that the current body of research presents is the variety of terms 18 that have been used when referring to growth, which include: "thriving" (Wadey & Hanton,19 2014), "perceived benefits" , "stress-related growth" (Galli & Vealey, 2008), 20…”
Section: Introductionmentioning
confidence: 99%
“…There is a consensus in the sport psychology literature that a measure of psychological resilience in athletes is needed to advance researchers' understanding of this desirable construct (Fletcher & Sarkar, 2012;Galli & Vealey, 2008;Gucciardi et al, 2011). Drawing on the broader psychometric literature in this area, this review has discussed a variety of measurement approaches and issues in the empirical study of resilience.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this proposition, it is worth noting that longitudinal studies are important in determining the stability of resilience across an individual's lifespan (Heller et al, 1999;Kinard, 1998;Luthar, 2006;Walsh et al, 2010;Windle, 1999). Indeed, in the sport psychology literature, there is a consensus that longitudinal research is needed to investigate resilient characteristics and performance throughout the entire process of managing potentially stressful situations (Fletcher & Sarkar, 2012;Galli & Vealey, 2008;Gucciardi et al, 2011). In relation to developing and validating a sport-specific measure of resilience, Gucciardi et al (2011) argued that it is crucial that researchers explore the factor structure stability and item consistency in a longitudinal fashion.…”
Section: Measuring Protective Factorsmentioning
confidence: 99%
See 1 more Smart Citation